2011
DOI: 10.5187/jast.2011.53.4.289
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameter Estimates for Meat Quality Traits in Berkshire Pigs

Abstract: Swine industry in Korea plays an important role in providing the meat for domestic consumption, and the number of pigs in Korea was about 9.72 million heads as of June, 2010. Meat quality is used to describe any traits which impact the consumer acceptability of fresh meat products. Meat color, firmness, water holding capacity, ultimate muscle pH24h (measured 24 hours post-mortem), shear force, and intramuscular fat percentage (IMF) are generally accepted as important indicators of meat quality and ultimately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Muscle pH is an important economic factor that is associated with water-holding capacity of muscle’s, which in turn has a marked influence on the appearance of meat ( Barge et al, 1991 ). According to Jung et al (2011) , pH 45min and pH 24min were positively correlated whereas both were negatively correlated with drip loss and shear force in Berkshire pigs. Previous studies have suggested the influence of MYC gene on glucose metabolism ( Collier et al, 2003 ), whereby lactic acid production from glycolysis reaction has an effect on the pH of meat.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Muscle pH is an important economic factor that is associated with water-holding capacity of muscle’s, which in turn has a marked influence on the appearance of meat ( Barge et al, 1991 ). According to Jung et al (2011) , pH 45min and pH 24min were positively correlated whereas both were negatively correlated with drip loss and shear force in Berkshire pigs. Previous studies have suggested the influence of MYC gene on glucose metabolism ( Collier et al, 2003 ), whereby lactic acid production from glycolysis reaction has an effect on the pH of meat.…”
Section: Resultsmentioning
confidence: 94%
“…A previous study reported that postmortem pH in muscle and meat quality characteristics correlated ( Huff-Lonergan et al, 2002 ). According to Jung et al (2011) , pH 45 min and pH 24 h were positively correlated whereas both were negatively correlated with drip loss and shear force in Berkshire pigs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“… Tomiyama et al (2011) reported 0.54 and 0.32 for (BF) at finish and CWT, respectively, in a Japanese Berkshire population (n = 4,773). Jung et al (2011) reported that heritabilities of pH2 4 h, CIE a, b, and L, WHC, NPPC marbling, drip loss, heat loss and shear force ranged between 0.51 and 0.66 in a Berkshire population (n = 808), Korea. Compared with the two reports, the heritability estimates of the meat quality traits in this study were low.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the heritability estimates reported for shear force and water holding capacity traits (Suzuki et al. (2005), Gjerlaug‐Enger, Aass, Odegård, and Vangen (2010), Jung, Kim, Park, Choi, and Park (2011), Miar et al. (2014), Baby et al.…”
Section: Discussionmentioning
confidence: 99%